Social Integration and Its Relationship To Motivational Traits (Self-Confidence As A Model) For Volleyball Players Sitting - Riyadh, Mohammed (JOM, 2023)
The sociology of sports sought to solve the social problems that confront sports, and to study the relationship between sports as a social phenomenon and between sports as a fact that overlaps in the structure and building of society, especially for the disabled, who have increased interest in them in the world recently. During his contacts with disabled athletes in the game of volleyball - sitting around Their capabilities and their possession of the motivational characteristics, as they suffer severely from neglect and marginalization by many of the state’s public and sports institutions .Which guarantees them the right to achieve their belonging within the team and the community, which caused from time to time a decline in their integration within the community, and the research aimed to build and codify Two scales(Social integration scale and statement scaletrait of self-confidence) for the players of clubs and sports committees in the southern and middle Euphrates regions for the disabled in Iraq, as well as the aim of the research to identify the correlation between social integration in terms of the characteristic of self-confidence, and the researcher assumed the emergence of different levels in the results of both measures. - As for the areas of research, the human field was the disabled players in volleyball _ sitting in sports committees and clubs in the southern regions and the middle Euphrates in Iraq, and the temporal field: 12/28/2021 to 3/8/2023 AD and the spatial field: clubs and sports halls for the southern region and the middle Euphrates in Iraq.